Core-shell structured quorum quenching beads for more sustainable anti-biofouling in membrane bioreactors. (1st March 2019) - Yu, Huarong; Lee, Kibaek; Zhang, Xiaolei; Choo, Kwang-Ho
Abstract: Efficient media designs for microbial quorum quenching (QQ) are essential to enable maximal biofouling control in membrane bioreactors (MBRs). Here we introduce a novel, double-layered, biocarrier design, which has QQ bacteria in the shell layer with biostimulating agents in the core, for effective membrane biofouling control. Confining the biostimulant within dense polymer materials permits its controlled release over an extended period. The provision of the biostimulant from the core to the outer shell, where the QQ bacteria are encapsulated, facilitates their prolonged survival and active life. The core-shell structured QQ bead with the stimulant inside, which inhibits biofilm formation, shows the best fouling mitigation in laboratory testing of MBRs, while enhancing signal molecule degradation and lowering exopolymer secretion. This new, layered QQ bead, which has dual functions of bioaugmentation and biostimulation, supports a highly efficient and sustainable anti-biofouling strategy. Graphical abstract: Highlights: A new, core-shell structured quorum quenching (QQ) bacteria carrier is investigated. An outer layer encapsulates QQ bacteria, while a dense core contains a biostimulant. Controlled release of the biostimulant prolongs the activity and survival of the QQ bacteria. This layered structure enables highly efficient and sustainable biofouling control. The QQ medium demonstrates the combined effects of bioaugmention and biostimulation.